Myths and Misconceptions about Intrauterine Devices: Impact on Usage - Emmanuel Lamptey; Michael A. Okunlola; Adesina Oladokun (Ital Publication, 2020)
The Intrauterine Devices (IUDs) have the benefit of providing long-term protection against unwanted pregnancies. This study investigates the myths and misconceptions associated with IUDs and their influence on the usage. This cross-sectional was conducted in six family planning centres in Accra. The questionnaire included statements of misconceptions about IUDs and participants responded either in agreement or in disagreement with each of the statements. Three hundred eligible respondents completed the questionnaire. The study commenced on January 2019 and ended on June 2019. We observed a heightening level of misconceptions about IUDs among the participants. Pain during insertion (68.7%), the male partner feeling it during intercourse (66.7%), IUDs breeding infections (66.3%) and the belief that it can damage the womb (65.7%) were the major misconceptions identified about the device. Although, these misconceptions may be the true reflection of the experiences of these users, an accurate knowledge about the device is still lacking which can influence the potential patronage. Massive education to change and dispels these misconceptions are needed.   Doi: 10.28991/SciMedJ-2020-0204-3 Full Text: PDF